Training on religious coping strategies for educators in the face of the Covid-19 pandemic - Eny Purwandari; Ajeng Nova Dumpratiwi; Daliman Daliman; Faruq Faruq; Fitriana Dwi Hastuti; Depy Eka Rachmawati (Universitas Muhammadiyah Magelang, 2022)
Covid-19 has changed the learning system to be online-based which makes educators experience stress and fatigue. This condition is caused by low knowledge of technology, criticism from students' parents, a learning atmosphere that is not conducive, limited access to home visits, until students are infected with Covid-19. The purpose of the training on religious coping strategies is to improve understanding of the coping strategies of educators during Covid-19. The training on religious coping strategies was carried out online assisted by zoom meeting software by involving 37 educators at the junior high, high and vocational levels consisting of 15 men and 22 women in the Surakarta Residency area. Activities carried out by pre-test, psychoeducation of religious coping, post-test, and program evaluation. The results of community service activities show an increase in the understanding and awareness of educators in dealing with the Covid-19 pandemic. The learning process with religious coping strategies makes mentally tougher to face the pandemic.